Accountability should precede the elections : address to the nation, October 1, 1977 - Zia-ul-Haq, Mohammad (Ministry of Information and Broadcasting, Directorate of Publications, Govt. of Pakistan, 1977)
Speech delivered by the Chief Martial Law Administrator of Pakistan.